2023
DOI: 10.1177/00222429231152880
|View full text |Cite
|
Sign up to set email alerts
|

What Holds Attention? Linguistic Drivers of Engagement

Abstract: From advertisers and marketers to salespeople and leaders, everyone wants to hold attention. They want to make ads, pitches, presentations, and content that captivates audiences and keeps them engaged. But not all content has that effect. What makes some content more engaging? A multi-method investigation combines controlled experiments with natural language processing of 600,000 reading sessions from over 35,000 pieces of content to examine what types of language hold attention and why. Results demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Lastly, future research could explore the effects of abstractness (vs concreteness) and narrativity on other outcomes. For example future studies may focus on metrics of attention (Berger et al ., 2023) or on the type of interaction generated by the content of communication, performing text analysis on the comments (e.g. Unnava and Aravindakshan, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, future research could explore the effects of abstractness (vs concreteness) and narrativity on other outcomes. For example future studies may focus on metrics of attention (Berger et al ., 2023) or on the type of interaction generated by the content of communication, performing text analysis on the comments (e.g. Unnava and Aravindakshan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer language research has demonstrated that linguistic features associated with emotions play an important role in driving user engagement (e.g. Berger et al, 2023). We consider the emotional tone of a text as a psycholinguistic variable, which summarizes the presence of positive and negative emotions in a text and varies from very negative tone to very positive tone.…”
Section: Ejim 279mentioning
confidence: 99%
“…These emerging approaches have the potential to shed light on a range of interesting questions (Berger et al, 2023; Berger & Packard, 2022; Boghrati et al, 2023). Take the ongoing debate about the universality of emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has used text mining to measure well-being in terms of positive and negative emotions, typically using the Linguistic Inquiry and Word Count (LIWC) dictionarybased technique to identify emotions such as anger, anxiety and sadness. However, concerns have been raised about the reliability of this approach for capturing unique emotions (Berger et al, 2023). Therefore, instead of using LIWC to measure followers' negative emotions and relied on an approach developed by Mohammad and Bravo-Marquez (2017) to measure anger, anxiety and sadness.…”
Section: Study Onementioning
confidence: 99%